Ethnobotanical study of the uses of medicinal plants in the Nasa ethnic group in the Colombian Andes - Paz Perafán, Gisela Mabel; Montenegro Paz, Gerardo (Instituto de Ecología, A.C., 2024)
Background and Aims: The main therapeutic sources of the traditional medicine of the Nasa ethnic group in the Colombian Andes is obtained from experts, midwives and traditional doctors (Thë’ Wala) located in the central mountain range of the Colombian Andes, which occupies an area of 25,400 hectares. Our ethnobotanical research is based on the hypothesis that Nasa traditional knowledge reveals crucial information about native species with therapeutic potential.Methods: All species collected were identified in the herbarium of the University of Cauca (CAUP). Total ailments were classified into 15 disease categories. The informant consensus factor (ICF) was employed to assess the degree and cultural relevance of the use of the taxa for the different disease categories. The use value (UV) index was applied to establish a consensus on the effectiveness of the species used to cure the different illnesses.Results: Our study reports 106 medicinal plants, belonging to 45 families. Asteraceae formed the most predominant family, followed by Lamiaceae. Ailments affecting the digestive system were the most frequently targeted group, making use of 26 plant species (24.5%). ICF values ranged between 0.96 and 1, with the highest values recorded for cancer and poisoning (1 each). Some plants are cultivated in the herb garden, or Tul, and others are collected in mountainous regions or in páramo (high moorland) areas, indicating the fragility of the pharmacopoeia in these regions. Conclusions: The findings of this study underline the importance of medicinal plants and their integral role in daily human activities and disease management of the Nasa ethnic group. Certain native species with high medicinal value, but sharply declining wild populations, ought to be studied for the purposes of resource assessment and conservation. Future research on the chemical composition and bioactivity of medicinal plants is needed.